2019
DOI: 10.3390/nu11123043
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Pattern with High Sugar Content Is Associated with Cardiometabolic Risk Factors in the Pomak Population

Abstract: The present study describes the geographically isolated Pomak population and its particular dietary patterns in relationship to cardiovascular risk factors. We collected a population-based cohort in a cross-sectional study, with detailed anthropometric, biochemical, clinical, and lifestyle parameter information. Dietary patterns were derived through principal component analysis based on a validated food-frequency questionnaire, administered to 1702 adult inhabitants of the Pomak villages on the Rhodope mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In terms of eating patterns, 44.7% of participants in our survey reported that they consumed sweets two to four times a day, indicating a worryingly high prevalence of sugar consumption. This result is in line with a study conducted in 2019 by Farmaki et al 19 which similarly found that young individuals often consume sugary meals. Finally, compared to studies by Hoeppner et al 20 and Eticha 21 , which found greater rates of smoking among college students, our study's results showed that 8.1% of participants reported smoking 20,21 .…”
Section: Discussionsupporting
confidence: 93%
“…In terms of eating patterns, 44.7% of participants in our survey reported that they consumed sweets two to four times a day, indicating a worryingly high prevalence of sugar consumption. This result is in line with a study conducted in 2019 by Farmaki et al 19 which similarly found that young individuals often consume sugary meals. Finally, compared to studies by Hoeppner et al 20 and Eticha 21 , which found greater rates of smoking among college students, our study's results showed that 8.1% of participants reported smoking 20,21 .…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a different cross-sectional study of our group identified similar associations between dietary patterns and biochemical biomarkers in the adults of the POMAK population. More specifically, the dietary pattern including increased consumption of products high in sugars was related to low levels of HDL cholesterol [27]. Similar trends were also noted when investigating the dietary patterns of adolescent populations, where a dietary pattern with high protein and animal fat content was associated with elevated levels of logBMI and logTriglycerides, in French teenagers [28].…”
Section: Discussionsupporting
confidence: 66%
“…The study includes biological sample collection for DNA extraction and lab-based blood measurements, and interview-based questionnaire filling. The phenotypes collected include anthropometric and biometric measurements, clinical evaluation data, biochemical and hematological profiles, self-reported medical history, demographic, socioeconomic and lifestyle information [ 11 , [13] , [14] , [15] , [16] , [17] , [18] ] [ 19 , 20 ]. The study was approved by the Harokopio University Bioethics Committee and informed consent was obtained from every participant.…”
Section: Methodsmentioning
confidence: 99%